Cross‐strand disulfides in the hydrogen bonding site of antiparallel β‐sheet (aCSDhs): Forbidden disulfides that are highly strained, easily broken. (17th December 2018) - Haworth, Naomi L.; Wouters, Michael J.; Hunter, Morgan O.; Ma, Lixia; Wouters, Merridee A.
Abstract: Some disulfide bonds perform important structural roles in proteins, but another group has functional roles via redox reactions. Forbidden disulfides are stressed disulfides found in recognizable protein contexts, which currently constitute more than 10% of all disulfides in the PDB. They likely have functional redox roles and constitute a major subset of all redox‐active disulfides. The torsional strain of forbidden disulfides is typically higher than for structural disulfides, but not so high as to render them immediately susceptible to reduction under physionormal conditions. Previously we characterized the most abundant forbidden disulfide in the Protein Data Bank, the aCSDn: a canonical motif in which disulfide‐bonded cysteine residues are positioned directly opposite each other on adjacent anti‐parallel β‐strands such that the backbone hydrogen‐bonded moieties are directed away from each other. Here we perform a similar analysis for the aCSDh, a less common motif in which the opposed cysteine residues are backbone hydrogen bonded. Oxidation of two Cys in this context places significant strain on the protein system, with the β‐chains tilting toward each other to allow disulfide formation. Only left‐handed aCSDh conformations are compatible with the inherent right‐handed twist of β‐sheets. aCSDhs tend to be more highly strained than aCSDns, particularly when both hydrogen bonds are formed. We discuss characterized roles of aCSDh motifs in proteins of the dataset, which include catalytic disulfides in ribonucleotide reductase and ahpC peroxidase as well as a redox‐active disulfide in P1 lysozyme, involved in a major conformation change. The dataset also includes many binding proteins.